Exposure of multidrug-resistant Klebsiella pneumoniae biofilms to 1,8-cineole leads to bacterial cell death and biomass disruption - Vázquez, Nicolás Martín (2022)
Klebsiella pneumoniae is a common cause of health-care associated infections. The rise of antibiotic resistance and the ability to form biofilm among K. pneumoniae strains are two key factors associated with antibiotic treatment failure. The present study investigates the antibiofilm activity of 1,8-cineole against preformed biofilms of multidrug-resistant extended-spectrum β-lactamase-producing K. pneumoniae clinical isolates. To evaluate the antibiofilm activity, cellular viability was analyzed by colony-forming units counting and live/dead staining. In addition, biofilm biomass was evaluated by crystal violet and the biofilm matrix was stained with calcofluor white and observed by confocal laser scanning microscopy. A time- and concentration-dependent effect of the phytochemical over biofilm cell viability was observed revealing that 1% (v/v) 1,8-cineole during 1 h was the optimal treatment condition displaying a significant reduction of cell viability in the preformed biofilms (2.5?5.3 log cfu/cm2). Furthermore, confocal laser scanning microscopy after SYTO-9 and propidium iodide staining showed that 1,8-cineole was capable of killing bacteria throughout all layers of the biofilm. The compound also caused a biofilm disruption (30?62% biomass reduction determined by crystal violet staining) and a significant decrease in biofilm matrix density. Altogether, our results demonstrate that 1,8-cineole is a promising candidate as a novel antibiofilm agent against multidrug-resistant K. pneumoniae strains producing extended-spectrum β-lactamases, given its capability to disrupt the structure and to kill cells within the biofilm.